Stable archaeal tetraether lipid liposomes for photodynamic application: transfer of carboxyfluorescein to cultured T84 tumor cells (Faculty of Medicine Universitas Indonesia, 2016)
Background: Archaeal membranes have phytanyl ether lipids instead of common fatty acid-glycerol esters in bacterial and eukaryotic cells. Sulfolobus and Thermoplasma species have unique membrane-spanning tetraether lipids (TEL), which form stable liposomes. Recently, we cultured Thermoplasma species from the Indonesian volcano Tangkuban Perahu and isolated TEL. The purpose of this in vitro study is to investigate the transfer of fluorescent dye from stable TEL liposomes to cultured colon carcinoma cells. Methods: TEL was extracted from cultured cells with chloroform-methanol (1:1), then it was fractionated and purified via diethylaminoethyl-cellulose-acetate columns and activated charcoal for the formation of stable liposomes. For the fluorescence exchange assay, TEL liposomes were loaded with water-soluble carboxyfluorescein (CF). Staining experiments were conducted with various cell cultures, and T84 colon carcinoma cells were chosen for the main experiments. Liposome stability was tested by light scattering and electron microscopic size determinations as well as by unspecific CF release at low pH (6.0–7.4)and increased temperature (4–50°C/70°C). Results: TEL liposomes exhibit high stability and extremely low proton permeability at low pH. CF staining of cultured T84 colon carcinoma cells appeares more intensive from TEL liposomes than from dipalmitoylphosphatidylcholine liposomes. Conclusion: The results of this in vitro study demonstrate CF staining of colon carcinoma cells and high stability of TEL liposomes at low pH, matching the condition in the gastro-intestinal (GI) route and in the urogentital (UG) tract. For this reason, in vivo studies on liposomal fluorescent photosensitizers for topical application of photodynamic cancer therapy in the GI and UG tracts should be carried out.